RANDOMIZED CONTROLLED TRIAL ACCELERATED HYPERFRACTIONATION RADIOTHERAPY CONCURRENT WITH CISPLATINUM VERSUS CONVENTIONAL RADIOTHERAPY FOR TREATING LOCALLY ADVANCED NASOPHARYNGEAL UNDIFFERENTIATED CARCINOMA - TJOKRONAGORO, Maesadjie (The ASEAN Journal of Radiology, 2023)
Background : Nasopharyngeal carcinoma (NPC) is the most frequent head and neck cancer, and a serious health problem in most radiotherapy centers in Indonesia Patients usually come when they are in locally advanced stage, with poor prognosis. Problem encountered in the bulky primary tumor and lymph node metastasis in the neck of the locally advanced stage III and IV, non distant metastasis, which is the majority of cases particularly in the hospitals in Indonesia. The result of the treatment with radiotherapy is unsatisfactory. For this reason, attention is being paid to the combined use of modified radiation therapy and chemotherapy for solving this problem Chemotherapy would probably increase the chances of local tumor control, either by (1) reducing cell burden in tumors undergoing radiotherapy, (2) rendering tumor cells more suspectible to radiation damage, or (3) spatially cooperating radiotherapy through its systemic action on micro metastastic disease. Objective : To investigate the efficacy of concurrent therapy Cisplatinum + accelerated hyperfractionation radiotherapy (C+AHR) for treatment of un differentiated type (WHO type III) carcinoma of the nasopharynx in locally advanced stage, compared to the treatment of conventional radiotherapy (CRT) Material and method : Randomized control trial is designed in two arms,: investigated arms consist of 55 cases of Nasopahryngeal carcinoma stage III and IV without distance metastasis, undifferentiated carcinoma histology, treated concurrently with Cisplatinum + accelerated hyperfractionation, radiotherapy (C+AHR), a two fraction dose per day, and the dose per fraction is 125 cGy, with the interval between fraction 4-6 hours to total dose equal with 70 Gy. Control arm consists of 55 cases NPC, treated with only conventional radiotherapy (CRT) of 70 Gy. Observation after treatment includes (1) Response of the primary tumor, (2) response of the lymph node metastasis in the neck, (3) relapse of the primary tumor and lymph node metastasis, (4) Duration of free disease interval. Result : (1) Response of the primary tumor : in the arm treated with Cisplatinum +radiotherapy accelerated hyperfractionation , complete response in the primary tumor is 52/55 (94.5%), compared to conventional Radiotherapy, wich is only 33/55 (58.9%). The differences of statistical analysis are significant (p < 0.001). (2) Response of the Lymph node metastasis : C + AHR : 47/55 (8.5%), CRT: 39/55 (69.6%) p=0. 131 (3) Relapse rate of the primary tumor : C+AHR : 10/55 (18.2%), CRT © 27/55 (48.2%) p= 0.007. (4) Relapse rate of lymph node metastasis in the neck :C+AHR = 13/55 (23. 6%), CRT 16/55 (28. 6%) p = 0.554 (5) Duration of relapse :C+ AHR : mean duration of local free relapse 17 2 months, and CRT : 9.11 months. F probability 0.003. This mean C+ AHR is able to inhibit the development of local relapse. Conclusion : Radiotherapy accelerated hyperfractionation, conncurrent with Cisplatinum for treament of local advanced Undifferentiated Carcinoma of the nasopharynx produce better result compared to the conventional fractionation of external radiotherapy, in terms of local response, relapse rate and disease free interval.